N/A: Air bubbles in blood gas syringe - Lippi, Giuseppe; Pighi, Laura; Salvagno, Gian Luca; Ferraro, Roberta; Celegon, Giovanni; Henry, Brandon M. (Journal of Medical Biochemistry, 2024)
Background. Minimizing air aspiration by carefully filling blood gas syringes is crucial to prevent air contamination from causing undesirable variations in gasses and other molecules. While some previous studies investigated this aspect, these are now outdated and only analyzed a limited number of blood gas parameters. Thus, we investigated the effects air contamination in the syringe using a modern blood gas analyzer. Methods. We sampled venous blood from 17 laboratory workers (mean age: 46±11 years; 10 women), filling two consecutive blood gas syringes. The first was filled exactly to its nominal volume (i.e., 1.0 mL), while the second was filled with 0.8 mL of blood and 0.2 mL of ambient air. Blood gas analysis was performed in each syringe using an identical analyzer. Results. In the syringe with the air bubble, we found statistically significant increase in pH (0.1%), pO2 (10.8%), SO2 (11.2%), total hemoglobin (3.0%), and hematocrit (2.7%), while values of pCO2 (-4.8%), sodium (-0.5%), and ionized calcium (-1.3%) were significantly reduced. With exception of pH, all these changes exceeded the performance specifications. Potassium, chloride, glucose, lactate, COHb and MetHb values remained unchanged. Conclusion. These findings confirm that air bubbles must be removed as soon as possible after sampling from blood gas syringes to prevent artifactual test results and misleading clinical judgment and inappropriate treatment. When blood gas syringes are received in the laboratory with air bubbles inside, the most vulnerable parameters (i.e., pO2, SO2, pCO2, sodium, ionized calcium, hematocrit and hemoglobin) should be suppressed.